2019
DOI: 10.1177/1049732319871251
|View full text |Cite
|
Sign up to set email alerts
|

Is Film as a Research Tool the Future of Public Health? A Review of Study Designs, Opportunities, and Challenges

Abstract: Among public health researchers, there is growing interest in film methods due to their ability to highlight subtleties in practices, capture emotions, engage hard-to-reach populations, and advocate for social change. Still, little is known about strengths and challenges associated with using film methods in public health. This review synthesizes peer-reviewed, public health research studies that apply film methods, and describes opportunities and challenges. Of the 3,431 identified articles, 20 met the inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…By recognizing photovoice as a single application of usefully creative, communicative mechanisms—which are available from many creative processes and interventions—health researchers will become better equipped to seek and utilize those forms of expression that are best suited to a given population or objective (see “Equity requires expressive options,” below). Indeed, Baumann and colleagues (2020) recently explored the benefits of film methods in public health research, noting that “more widespread use of such methods is long overdue” (p. 6).…”
Section: Photovoice Limitations: Unrecognized As An Arts-based Researmentioning
confidence: 99%
See 1 more Smart Citation
“…By recognizing photovoice as a single application of usefully creative, communicative mechanisms—which are available from many creative processes and interventions—health researchers will become better equipped to seek and utilize those forms of expression that are best suited to a given population or objective (see “Equity requires expressive options,” below). Indeed, Baumann and colleagues (2020) recently explored the benefits of film methods in public health research, noting that “more widespread use of such methods is long overdue” (p. 6).…”
Section: Photovoice Limitations: Unrecognized As An Arts-based Researmentioning
confidence: 99%
“…This concern can be mitigated by emphasizing transparency and accuracy in the description, practice, and dissemination of photovoice and its results. In addition, continued modifications and developments of the method will help increase its capacity to center diverse communities across multiple research stages (Baumann et al, 2020;Castleden & Garvin, 2008;Stanton, 2014).…”
Section: Centering Communities?mentioning
confidence: 99%
“…However, having extra time in the community and spending time with the families during the filmmaking process turned out to be a positive experience for us as researchers to generate a deeper understanding of families’ beliefs and of the village context in which these practices were unfolding. While the method is time-intensive, this limitation should be weighed with the many strengths it provides; the time investment is similar to other qualitative research methodologies (Baumann, et al, 2019). In addition, equipment and training costs can be high; fortunately affordable, durable, and easy-to-use options are on the rise.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of visual and arts-based research methods are well established in several disciplines, but film methods in particular are yet to be widely embraced in health research. According to a 2019 literature review, 20 research articles were identified that applied filmmaking research methods for generating health-related knowledge (Baumann, et al, 2019). The studies used film techniques to explore a range of public health topics including asthma (Gupta et al, 2013; Warren et al, 2016), adolescent health (Akre et al, 2015; Chung et al, 2013), vaccination (Lundström et al, 2012), and mental health (Mirza et al, 2017; Petros et al, 2016), among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation